APLIKASI SimDif (Simple Different): MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEBSITE UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INGGRIS - Ardhianti, Novika Ayu (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
This study was prompted by the low level of student interest in learning English at SMKS Pancasila 3 Baturetno. The purpose of this research is to examine the impact of utilizing the SimDif application as an interactive, website-based learning medium on enhancing students’ motivation and participation in English learning. A descriptive quantitative approach was employed, with the independent variable being the use of the SimDif application and the dependent variables comprising students’ learning interest and participation. Data were collected through classroom observations and the administration of questionnaires before and after the intervention. The data were analyzed descriptively using percentage analysis to determine changes in students’ motivation and participation levels. The findings indicate a positive shift in both variables following the implementation of SimDif as a learning tool. The results show a significant improvement in students' motivation to learn. The class average score increased by 20%, and the active participation of students in discussions and online tasks increased by 30%. Students also found it easier to understand concepts due to the visual display and interactive quiz features. The use of SimDif not only creates a more enjoyable learning experience but also builds students' digital skills, in line with the demands of the 4.0 industrial era. The integration of technology in learning has proven to enrich the teaching and learning process, enhance student engagement, and support independent learning. Regular evaluation and further development are recommended so that this application can be consistently applied across various subjects for broader benefits.